Determination of risks of lower adherence to CPAP treatment before their first use by patients. (January 2022) - Bros, Julie; Poulet, Caroline; Methni, Jonathan El; Deschaux, Chrystèle; Gandit, Marc; Pauwels, Petrus J; Charavel, Marie
A better understanding of Continuous Positive Airway Pressure (CPAP) adherence is a priority in improving patient care. To Identify adherence typology with a longitudinal approach, and explore the early determinants of lower adherence to CPAP. Obstructive sleep apnea patients ( N = 204). Prospective and longitudinal study.A classification into four profiles was observed: " Regular Adherents, " " Non-Regular Adherents, " " Persistent Non-Adherents, " and " Non-Persistent Non-Adherents ." Specific biopsychosocial factors make it possible to evaluate the risk of belonging to a lower adherence profile. We propose a novel approach of CPAP treatment adherence. Several pre-determinants have been identified.